Fine-Scale Position Effects Shape the Distribution of Inversion Breakpoints in Drosophila melanogaster. (21st May 2020) - McBroome, Jakob; Liang, David; Corbett-Detig, Russell
Abstract: Chromosomal inversions are among the primary drivers of genome structure evolution in a wide range of natural populations. Although there is an impressive array of theory and empirical analyses that have identified conditions under which inversions can be positively selected, comparatively little data are available on the fitness impacts of these genome structural rearrangements themselves. Because inversion breakpoints can disrupt functional elements and alter chromatin domains, the precise positioning of an inversion's breakpoints can strongly affect its fitness. Here, we compared the fine-scale distribution of low-frequency inversion breakpoints with those of high-frequency inversions and inversions that have gone to fixation between Drosophila species. We identified a number of differences among frequency classes that may influence inversion fitness. In particular, breakpoints that are proximal to insulator elements, generate large tandem duplications, and minimize impacts on gene coding spans which are more prevalent in high-frequency and fixed inversions than in rare inversions. The data suggest that natural selection acts to preserve both genes and larger cis -regulatory networks in the occurrence and spread of rearrangements. These factors may act to limit the availability of high-fitness arrangements when suppressed recombination is favorable.